2010
DOI: 10.1007/s11116-010-9299-4
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the time frame for the transition from leisure-cyclist to commuter-cyclist

Abstract: Commuter-cyclist, Leisure-cyclist, Hazard, Duration, Covariate effect,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
2
10
1
1
Order By: Relevance
“…This finding conflicts with several previous studies in which researchers have suggested that cycling for leisure or sport may have a positive effect on cycle commuting (Kroesen & Handy, 2013;Lee, Park, & Sohn, 2012;Park, Lee, Shin, & Sohn, 2011;Stinson & Bhat, 2004;Xing, Handy, & Mokhtarian, 2010). The explanation for this result may lie in the image of cycle commuting which, in countries where cycling is uncommon, is viewed as dangerous, demanding and stressful; often in contrast to leisure cycling which is regarded as calm, peaceful and liberating (Gardner, 1998).…”
Section: Carcontrasting
confidence: 67%
“…This finding conflicts with several previous studies in which researchers have suggested that cycling for leisure or sport may have a positive effect on cycle commuting (Kroesen & Handy, 2013;Lee, Park, & Sohn, 2012;Park, Lee, Shin, & Sohn, 2011;Stinson & Bhat, 2004;Xing, Handy, & Mokhtarian, 2010). The explanation for this result may lie in the image of cycle commuting which, in countries where cycling is uncommon, is viewed as dangerous, demanding and stressful; often in contrast to leisure cycling which is regarded as calm, peaceful and liberating (Gardner, 1998).…”
Section: Carcontrasting
confidence: 67%
“…Thus, Park et al mention that 57% of commuter cyclists began as leisure cyclists (31). However, the increase in the number of commuting trips must come from motorized trips so as to maintain high levels of Ps and PT users.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
“…Recreational cyclists (those who cycle for fun or exercise) make a logical target group for promoting everyday utility cycling as they have the motivation, equipment and skill for cycling. 5 To understand whether motivations for utility cycling are changing, it is useful to examine the motivations of these cyclists. The aim of this qualitative study was to draw on the lived experiences of recreational cyclists to understand what they perceive to be the major influences on motivation for utility cycling.…”
Section: Introductionmentioning
confidence: 99%